Aminophylline and increased activity of peripheral chemoreceptors in newborn infants. Issue 1 (July 1993) - Cattarossi, L; Rubini, S; Macagno, F
Abstract : Peripheral chemoreceptor activity was studied in nine healthy, unsedated neonates (with a mean (SD) postconceptional age of 39 (2) weeks and birth weight of 3000 (400) g) by measuring the inhibition of ventilation elicited by five breaths of 100% oxygen (Dejours technique). Changes in tidal volume, frequency, and minute ventilation were measured before and after administration of aminophylline (10 mg/kg by mouth). Before aminophylline hyperoxia induced a decrease in minute ventilation (from a mean (SE) of 825 (55) to 520 (30) ml/kg/min) as result of reduction of tidal volume (from 12 (0.3) to 8 (0.3) ml/kg). After aminophylline administration the hyperoxia induced decrease in tidal volume (from 14 (0.7) to 6 (0.3) ml/kg) and minute ventilation (from 847 (57) to 386 (21) ml/kg/min) was significantly greater than before. It is concluded that in neonates peripheral chemoreceptors are more active in the presence of aminophylline. It is speculated that aminophylline increases the activity of peripheral chemoreceptors, reducing the breakdown of cAMP, which is a crucial mediator for peripheral chemoreceptor discharge.